PERBEDAAN PEMBERIAN AROMATERAPI LEMON DAN AROMATERAPI LAVENDER TERHADAP NYERI HAID (DISMENORE) PADA REMAJA PUTRI - Helmia Meinika; Lusi Andriani (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Prevalence of dysmenorrhea According to data from the World Health Organization (WHO), the incidence was 1,769,425 (90%) of women with dysmenorrhea, with 10-15% experiencing severe dysmenorrhea. Pain management can be done pharmacologically and non pharmacologically, non-pharmacologically, one of which is aromatherapy. The Aim Of The Research: This study aims to determine the differences in giving lemon aromatherapy and lavender aromatherapy on menstrual pain (dysmenorrhea) in adolescent girls in the working area of ​​the Kuala Lempuing Community Health Center, Bengkulu City. Research Method: This type of research is a Quasi Experiment with a two group pretest-postest research method design. Data analysis used Wilcoxon test and Mann-Whitney test. The Result: The Wilcoxon test results showed a p-value of 0.000 (<0.05) which means that there is a difference in the level of dysmenorrhea pain after giving lemon aromatherapy and the Wilcoxon results in the lavender aromatherapy group showed a p-value of 0.000 (<0.05) which means that there is a difference in the level of dysmenorrhea pain. after giving lavender aromatherapy. The results of the Mann-Whitney test analysis showed a P-value of 0.273 (> 0.005). From the above results, it is known that there is no difference in giving lemon aromatherapy and lavender aromatherapy to the level of dysmenorrhea pain in young women. Conclusions: It is hoped that young women in the Kuala Lempuing Health Center working area who experience dysmenorrhea can use lemon aromatherapy and lavender aromatherapy to reduce the level of dysmenorrhea pain. Keywords: Lemon Aromatherapy, Lavender Aromatherapy, Dysmenorrhea Pain